2008
DOI: 10.1124/jpet.108.140889
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CYP4A1 in U251 Human Glioma Cell Induces Hyperproliferative Phenotype in Vitro and Rapidly Growing Tumors in Vivo

Abstract: Exogenous 20-hydroxyeicosatetraenoic acid (20-HETE) increases the growth of human glioma cells in vitro. However, glioma cells in culture show negligible 20-HETE synthesis. We examined whether inducing the expression of a 20-HETE synthase in a human glioma U251 cell line would increase proliferation. U251 cells transfected with CYP4A1 cDNA (termed U251 O) increased the formation of 20-HETE from less than 1 to over 60 pmol/min/mg proteins and increased their proliferation rate by 2-fold (p Ͻ 0.01). Compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 32 publications
2
41
0
6
Order By: Relevance
“…EC proliferation was mediated by VEGF, which increases after the stimulation of ECs with 20-HETE (8, 23). 20-HETE not only induces increases in ECs but also in other cells (24). In the present study, we showed in ECs maintained under normal oxygen conditions that 20-HETE causes the upregulation of HIF-1␣.…”
Section: Discussionsupporting
confidence: 64%
“…EC proliferation was mediated by VEGF, which increases after the stimulation of ECs with 20-HETE (8, 23). 20-HETE not only induces increases in ECs but also in other cells (24). In the present study, we showed in ECs maintained under normal oxygen conditions that 20-HETE causes the upregulation of HIF-1␣.…”
Section: Discussionsupporting
confidence: 64%
“…In 2008, U251 glioblastoma cells were genetically altered (transfected with rat CYP4A1 cDNA) to increase the formation of 20-HETE (156). This stimulated tumor cell proliferation in culture.…”
Section: Cytochrome P450-derived Eicosanoids and Cancermentioning
confidence: 99%
“…In some experiments VSMCs were treated with dinitrochlorobenzene (CDNB) (0.15μM). Concentrations of pharmacological inhibitors used have been shown to be effective and specific (27)(28)(29). …”
Section: Introductionmentioning
confidence: 99%